Certain Subclasses of p-Valent Meromorphic Functions Associated with a New Operator. (3rd April 2013) - Mostafa, A. O.; Aouf, M. K.; Shamandy, A.; Adwan, E. A.
Abstract : We introduce two classes of p -valent meromorphic functions associated with a new operator and derive several interesting results for these classes.